3D-printed activated carbon for post-combustion CO2 capture - Zafanelli, Lucas F.A.S.; Henrique, Adriano; Steldinger, Hendryk; Diaz de Tuesta, Jose L.; Gläsel, Jan; Rodrigues, Alírio E.; Gomes, Helder T.; Etzold, Bastian J.M.; Silva, José A.C. (Microporous and Mesoporous Materials, 2022)
The applicability of 3D-printed activated carbons for their use to CO2 capture in post-combustion streams and the influence of activation conditions on CO2 uptake and CO2 to N2 selectivity were studied. For two monoliths with the same open cellular foam geometry but low and high burnoff during activation, a series of fixed-bed breakthrough adsorption experiments under typical post-combustion conditions, in a wide range of temperature (313 and 373 K), and partial pressure of CO2 up to 120 kPa were carried out. It is shown that the higher burnoff during activation of the 3D printed carbon enhances the adsorption capacity of CO2 and N2 due to the increased specific surface area with sorption uptakes that can reach 3.17 mol/kg at 313 K and 120 kPa. Nevertheless, the lower burnoff time on monolith 1 leads to higher selectivity of CO2 over N2, up to 18 against 10 on monolith 2, considering a binary interaction to a mixture of CO2/N2 (15/85 vol%) at 313 K. The single and multicomponent adsorption equilibrium is conveniently described through the dual-site Langmuir isotherm model, while the breakthrough curves simulated using a dynamic fixed-bed adsorption linear driving force model. Working capacities for the 3D printed carbon with lower burnoff time lead to the best results, varying of 0.15–1.1 mol/kg for the regeneration temperature 300–390 K. Finally, consecutive adsorption-desorption experiments show excellent stability and regenerability for both 3D printed activated carbon monoliths and the whole study underpins the high potential of these materials for CO2 capture in post-combustion streams.
CRIS-Team Scopus Importer:2023-08-15
Keywords: 3D printed monoliths; Fixed bed adsorption; Multi-component adsorption; Numerical modeling; Post-combustion CO

3D printed photopolymer derived carbon catalysts for enhanced wet peroxide oxidation - Silva, Adriano S.; Diaz de Tuesta, Jose L.; Henrique, Adriano; Roman, Fernanda F.; Omralinov, Daria; Steldinger, Hendryk; Gläsel, Jan; Etzold, Bastian; Silva, Jose A.C.; Silva, Adrián M.T.; Pereira, Ana I.; Gomes, Helder T. (Chemical Engineering Journal, 2024)
In this paper, we explore the application of powdered carbon and 3D-printed carbon monoliths prepared by carbonization of a tailored photopolymer. We demonstrate the efficiency of the developed carbonaceous samples in removing paracetamol (PCM) and sulfamethoxazole (SMX), used as model contaminants. Our results demonstrate that carbon samples are active in CWPO, and their catalytic activity is significantly improved by applying nitric acid and urea functionalization methods. The characterization results showed the pure carbon nature of the material (no ashes), their unique structure defects proven by Raman (D/G > 1.8), textural properties (SBET = 291–884 m2/g) and their surface chemistry, which was addressed by pHPZC (2.5–7.5), acidity (312–2375 µ mol gcat−1) and basicity (117–653 µ mol gcat−1) determination and XPS of highlighted materials (N1s = 0–3.51 at.%, O1s = 7.1–15.3 at.%). Using desorption assays, our study reveals the adsorption role for pollutant degradation by CWPO using carbon monolithic samples. At last, we demonstrated the ability of functionalized 3D-printed carbon monoliths to keep degradation of PCM and total organic carbon (TOC) above 85 % and 80 %, respectively, during 48 h in a continuous flow CWPO system. Sulfamethoxazole degradation in continuous system was also studied to validate the catalyst versatility, achieving 81 % and 79 % pollutant degradation and TOC abatement, respectively, during 48 h on stream. The characterization of the recovered catalyst provides further insights into the absence of structural modifications after the reaction, reinforcing the stability and reusability characteristic of the 3D-printed carbon catalyst.
Created from Fastlane, Scopus look-up
Keywords: 3D-printing; Acetaminophen; Advanced oxidation processes (AOPs); Contaminants of emerging concern (CECs); Fenton-like; Metal-free monoliths

Activated Carbon in the Third Dimension—3D Printing of a Tuned Porous Carbon - Steldinger, Hendryk; Esposito, Alessandro; Brunnengräber, Kai; Gläsel, Jan; Etzold, Bastian J.M. (Advanced Science, 2019)
A method for obtaining hierarchically structured porous carbons, employing 3D printing to control the structure down to the lower µm scale, is presented. To successfully 3D print a polymer precursor and transfer it to a highly stable and structurally conformal carbon material, stereolithography 3D printing and photoinduced copolymerization of pentaerythritol tetraacrylate and divinylbenzene are employed. Mechanically stable structures result and a resolution of ≈15 µm is demonstrated. This approach can be combined with liquid porogen templating to control the amount and size (up to ≈100 nm) of transport pores in the final carbonaceous material. Additional CO2 activation enables high surface area materials (up to 2200 m2 g-1) that show the 3D printing controlled µm structure and nm sized transport pores. This unique flexibility holds promise for the identification of optimal carbonaceous structures for energy application, catalysis, and adsorption.
CRIS-Team Scopus Importer:2023-08-15
Keywords: 3D printing; activated carbon; CO; porogen templating; stereolithography

Aqueous-phase reforming of alcohols with three carbon atoms on carbon-supported Pt - Godina, Lidia I.; Tokarev, Anton V.; Simakova, Irina L.; Mäki-Arvela, Päivi; Kortesmäki, Ewelina; Gläsel, Jan; Kronberg, Leif; Etzold, Bastian J.M.; Murzin, Dmitry Yu (Catalysis Today, 2018)
Aqueous-phase reforming of propanol-1, propane-1,2-diol and glycerol was performed at 498 K and 29.7 bar in a continuous reactor with platinum supported on a polymer-derived carbon, as a catalyst. The number of hydroxyl groups of the reactant influenced the product distribution. An unexpectedly long stabilization period − more than 150 h of time-on-stream − was found to be an important feature of the catalyst.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Aqueous-phase reforming; Carbon support; Glycerol; Platinum; Propane-1; 2-diol; Propanol-1

Can Temperature-Programmed Techniques Provide the Gold Standard for Carbon Surface Characterization? - Herold, Felix; Gläsel, Jan; Etzold, Bastian J.M.; Rønning, Magnus (Chemistry of Materials, 2022)
Due to their chemical and thermal stability, electrical conductivity, and high specific surface areas, nanocarbons and porous carbon materials have found use in numerous key applications within the current transition of energy and raw-material sources. Since all these applications rely on multiphase interactions between the carbon surface and surrounding solid, liquid, or gaseous phases, carbon surface chemistry is elevated to a critical factor of influence. However, the characterization of carbon surface chemistry is notoriously complex, involving carbon defect sites and chemically similar heteroatom species in a wide range of different binding states and chemical environments. Due to this high degree of complexity, a comprehensive characterization of carbon surface species and reactivity is a major challenge for which there is no analytical "silver bullet" but is fundamental to the rational development of advanced functional carbon materials. In this context we would like to highlight the potential of temperature-programmed techniques (TPX) for carbon surface analytics, which benefit from widely available, easy-to-handle equipment and offer information on the identity, quantity, and reactivity of surface species. Hence, this article reviews the state of the art concerning temperature-programmed techniques for carbon surface characterization, focusing not only on the qualitative and quantitative analysis of carbon surface species but also on the unique ability of temperature-programmed methods to assess carbon surface reactivity. In this context, progress made so far in temperature-programmed desorption, temperature-programmed reduction, and temperature-programmed surface reactions is discussed, highlighting pitfalls and gaps in knowledge. Based on this foundation, strategies for the further development of temperature-programmed methods for carbon surface analysis are proposed, aiming to establish TPX as the future gold-standard in carbon surface characterization.
CRIS-Team Scopus Importer:2023-08-15

Carbon-Methanol Based Adsorption Heat Pumps: Identifying Accessible Parameter Space with Carbide-Derived Carbon Model Materials - Träger, Lisa; Gläsel, Jan; Scherle, Marc; Hartmann, Julian; Nieken, Ulrich; Etzold, Bastian J.M. (Chemical Engineering & Technology, 2020)
In adsorption heat pumps, the properties of the porous adsorbent and the refrigerant determine the performance. Major parameters for this working pair are the total uptake of the adsorptive, its kinetics, and the heat transfer characteristics. In the technical application despite powdered adsorbents, thin consolidated layers of the adsorbent can be attractive and obtained by a binder-based approach but likely result in competing material properties. Thus, for a process optimization, the accessible parameter space and interdependencies have to be known and were deduced in this work for model porous carbons (carbide-derived carbons derived from TiC and ZrC) and methanol as well as the addition of different amounts of boron nitride, silver, and graphite as heat-conductive agents and the use of two binders.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Adsorption heat pump; Carbide-derived carbon; Carbon-methanol; Consolidated carbon plate; Model carbon material

Controlled synthesis of core-shell carbide-derived carbons through in situ generated chlorine - Ariyanto, Teguh; Zhang, Guirong; Riyahi, Farshad; Gläsel, Jan; Etzold, Bastian (Carbon, 2017)
Core-shell porous carbon represents an innovative concept for optimizing performances of carbon materials in a wide range application. Here, a novel route to produce carbons with spatially varying pore and microstructure is presented. Following the carbide-derived carbon method, a homogeneous and adjustable shell generation is achieved through mixing a limited amount of solid chlorine precursors with titanium carbide raw material. Chlorine is released in situ when reaching approx. 600 °C and consumed subsequently directly, resulting in the aspired materials. Various characterization methods proved that the amount of solid chlorine precursor directly adjusts the share of the shell for the core-shell material, while a range of 5–80% was studied. The amorphous, microporous shell can be converted to a mesoporous and graphitic shell (crystal sizes 20 nm), through a subsequent vacuum annealing, allowing to control the properties of the carbon shell. The carbon core results after a subsequent second chlorination step, where directly gaseous chlorine is used. The materials were characterized in detail after every step of this novel route. Adjusting the share between mesoporous/graphitic shell and microporous/amorphous core for these new materials is of interest in applications where competing processes like mass transfer and surface interaction need to be optimized.
CRIS-Team Scopus Importer:2023-08-15

Controlled synthesis of PVP-based carbon supported Ru nanoparticles: Synthesis approaches, characterization, capping agent removal and catalytic behavior - Simakova, I. L.; Demidova, Yu S.; Gläsel, Jan; Murzina, E. V.; Schubert, T.; Prosvirin, I. P.; Etzold, Bastian J.M.; Murzin, D. Yu (Catalysis: Science and Technology, 2016)
Polyvinylpyrrolidone (PVP) stabilized Ru nanoparticles (NPs) with the mean size ca. 2.4 nm were synthesized and immobilized on mesoporous Sibunit, macroporous carbon nanofibers of platelet structure (CNF-Pl) and micro-/mesoporous TiC carbide-derived carbon (CDC) providing 1.7-2.9 wt.% Ru/C catalysts with the mean Ru size 2.1-2.7 nm. The presence of PVP on the catalyst surface drastically diminished activity in structure sensitive galactose to galactitol hydrogenation. Different PVP removal and support modification methods were tested to elucidate the effect of support hydrophilicity/ hydrophobicity, preliminary support functionalization, additional Ru NPs washing prior to immobilization as well as PVP removal degree on catalytic behavior. For characterization of the carbon supports and synthesized catalysts TEM, XPS, XRD, XRF, water adsorption/desorption experiments and N2 physisorption were applied. Carbon supports were functionalized before Ru NPs immobilization by treatment with 5 wt.% HNO3, HNO3 conc., Ar (700oC), air (350oC), H2 (700oC) without visible support microstructure alterations. Several protocols for PVP removal were applied such as solvothermal (with water and acetic acid aqueous solutions at 220°C) and thermal treatment (in air, argon, hydrogen or nitrogen at different temperatures) not resulting in noticeable changes in Ru NPs size. The thermal treatment in air at 180°C followed by reduction at 250°C was found to be more effective in the case of Sibunit and CNF-Pl while solvothermal treatment in water at 220°C (PN2 25 bar) improved significantly the activity of TiC-CDC based catalysts. Untreated Sibunit and CNF-Pl carbon supports provided higher activity in galactose hydrogenation with Ru/Sibunit exhibiting the best catalytic activity being also the most hydrophilic according to water sorption isotherms. Catalytic activity of untreated micro-/mesoporous Ru/TiC-CDC increased noticeably depending on the support pretreatment in the row: untreated < 5% HNO3 < HNO3 conc. Additional TiC-CDC support functionalization was proposed to be required because of a relatively low amount of oxygen-containing groups on the surface compared to Sibunit and CNF.
CRIS-Team Scopus Importer:2023-08-15
Keywords: biomass; carbon support; colloidal synthesis; galactose hydrogenation; nanoparticles; PVP removal; ruthenium

Highly efficient removal of pharmaceuticals from water by well-defined carbide-derived carbons - Álvarez-Torrellas, Silvia; Munoz, Macarena; Gläsel, Jan; de Pedro, Zahara M.; Domínguez, Carmen M.; García, Juan; Etzold, Bastian J.M.; Casas, Jose A. (Chemical Engineering Journal, 2018)
In this work, we evaluate the feasibility of carbide-derived carbons (CDCs) as reliable and highly efficient adsorbents for the removal of pharmaceuticals from water. CDCs were produced from titanium carbide at temperatures within the range of 800–1400 °C employing chlorine as extraction agent. The materials were physicochemically characterized and tested in the adsorption of two relevant pharmaceuticals (diclofenac (DCF) and metronidazole (MNZ)) in aqueous solutions. We found that the specific surface area in combination with a low functionalized surface plays a key role on the adsorption capacity of the material while the average pore size determines the kinetics of the process. Notably, the CDCs showed an outstanding adsorptive behaviour compared to different conventional carbon materials under the same operating conditions, which was attributed not only to their high surface areas but mainly to their strong hydrophobic properties. The optimum material (specific surface area of 1676 m2 g−1) showed extremely high adsorption capacity values (551 and 410 mg g−1 for DCF and MNZ, respectively). Remarkably, the process was very fast (10 min of equilibrium time) even using low doses of adsorbent (0.3 mg mL−1). The performance of the optimum CDC was also demonstrated in bi-component systems while its versatility was demonstrated in a real wastewater treatment plant (WWTP) effluent, obtaining a good performance in terms of adsorption capacity (up to ∼400 mgDCF g−1) and kinetics (equilibrium time of 10 min). These results demonstrate the promise of CDCs for reliable, effective and fast flow-through tertiary water treatment.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Adsorption; Carbide-derived carbons; Pharmaceuticals; Water treatment

Improving control of carbide-derived carbon microstructure by immobilization of a transition-metal catalyst within the shell of carbide/carbon core shell structures - Ariyanto, Teguh; Gläsel, Jan; Kern, Andreas; Zhang, Guirong; Etzold, Bastian (Beilstein Journal of Nanotechnology, 2019)
Carbon materials for electrical energy devices, such as battery electrodes or fuel-cell catalysts, require the combination of the contradicting properties of graphitic microstructure and porosity. The usage of graphitization catalysts during the synthesis of carbide-derived carbon materials results in materials that combine the required properties, but controlling the microstructure during synthesis remains a challenge. In this work, the controllability of the synthesis route is enhanced by immobilizing the transition-metal graphitization catalyst on a porous carbon shell covering the carbide precursor prior to conversion of the carbide core to carbon. The catalyst loading was varied and the influence on the final material properties was characterized by using physisorption analysis with nitrogen as well as carbon dioxide, X-ray diffraction, temperature-programmed oxidation (TPO), Raman spectroscopy, SEM and TEM. The results showed that this improved route allows one to greatly vary the crystallinity and pore structure of the resulting carbide-derived carbon materials. In this sense, the content of graphitic carbon could be varied from 10-90 wt % as estimated from TPO measurements and resulting in a specific surface area ranging from 1500 to 300 m(2)g(-1).
CRIS-Team WoS Importer:2019-02-21

Mesoporous and crystalline carbide-derived carbons: Towards a general correlation on synthesis temperature and precursor structure influence - Christians, Hauke; Brunnengräber, Kai; Gläsel, Jan; Etzold, Bastian J.M. (Carbon, 2021)
Carbide-derived carbons (CDCs) comprise a promising group of porous carbons and already proofed to be excellent model materials due to their remarkable tuneability of pore structure and crystallinity via choice of synthesis parameters. Most studies focused on microporous, high surface area materials and mainly amorphous materials at synthesis temperatures up to 1200 °C. While studies showed for TiC that higher temperatures may lead to more crystalline and mesoporous structures, which are highly attractive for electrochemical applications, these regime and CDC materials are only rarely studied. Thus, it stays an open question how the interplay of carbide precursor and temperature above 1200 °C influence the resulting carbon structure. Therefore, this work investigated the structure of CDCs synthesized at high temperatures (800–1600 °C) from six different carbides (NbC, SiC, TaC, TiC, VC, ZrC). Accordingly, for rock salt type carbides with carbon to carbon distances above 0.334 nm a direct correlation between carbide precursor structure and resulting carbon structure could be found, while for SiC with a hexagonal close-packed structure and carbon to carbon distance below 0.334 nm more crystalline and mesoporous structures only result at temperatures above 1600 °C. The raw characterization data is provided through an open access repository.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; Crystalline; Mesoporous; Precursor structure

Mesoporous and Graphitic Carbide-Derived Carbons as Selective and Stable Catalysts for the Dehydrogenation Reaction - Gläsel, Jan; Diao, Jiangyong; Feng, Zhenbao; Hilgart, Markus; Wolker, Thomas; Su, Dang Sheng; Etzold, Bastian (Chemistry of Materials, 2015)
Dehydrogenation of ethylbenzene to styrene is one of the most important catalytic processes in chemical industry. While it was demonstrated that nanocarbons like nanotubes, nanodiamond, or nanographite show high performance, especially selectivity, these powders give rise to handling problems, high pressure drop, hampered heat and mass transfer, and unclear health risks. More common macroscopic carbon materials like activated carbons show unsatisfying selectivity below 80%. In this study, mesoporous, graphitic, and easy to handle carbon powders were synthesized on the basis of the reactive extraction of titanium carbide in a novel temperature regime. This resulted in extraordinary properties like a mean pore diameter of up to 8 nm, pore volumes of up to 0.90 mL g-1, and graphite crystallite sizes exceeding 25 nm. Exceptional styrene selectivities of up to 95% were observed for materials synthesized above 1300 °C and pretreated with nitric acid. Furthermore, the long-term stability of these non-nanocarbon catalysts could be demonstrated for the first time during 120 h of time-on-stream. (Figure Presented).
CRIS-Team Scopus Importer:2023-08-15

Preparation of carbide-derived carbon supported platinum catalysts - Hasse, Benjamin; Gläsel, Jan; Kern, Andreas; Murzin, D. Yu.; Etzold, Bastian (Catalysis Today, 2015)
Well defined carbon supported catalysts are of interest to deduce structure activity relationships and for catalyst optimization. Carbide-derived carbons (CDC) are high purity porous carbons with tunable pore structure. The deposition of platinum on silicon and titanium carbide based CDC was studied, using a three step process of acid treatment, ion-adsorption of platinum precursor and gas phase reduction. The influence of the steps on the carbon support properties and possibility to control the platinum loading and resulting cluster size was determined. Most crucial is the acid treatment step, where oxygen groups are introduced. At a too high degree of functionalization (non-carbon content above 30 wt%), which can result for nitric acid treatment, the pore structure is heavily attacked. For sulfuric acid treatments non-carbon contents below 15 wt% and only minor changes in the pore structure were observed. The ion-adsorption technique could be successfully transferred to the CDC supports. For medium to high degrees of functionalization (non-carbon contents above 20 wt%) the full deposition of 2.5 wt% of platinum was achieved. By the choice of platinum precursor, the pH of impregnation and the temperature of reduction the platinum cluster size could be varied from 2.5 to 5.3 nm. Thus, important knowledge how to prepare tuned Pt/C catalysts based on CDC and the ion-adsorption technique could be deduced.
EAM Import::2019-03-08

Producing high quality carbide-derived carbon from low quality byproducts stemming from SiC production - Ariyanto, Teguh; Mohd Laziz, Afiq; Gläsel, Jan; Zhang, Guirong; Garbes, Josef; Etzold, Bastian (Chemical Engineering Journal, 2016)
The utilization of carbide-derived carbons (CDCs) in a wide range of applications is obstructed due to relatively high production costs. In this study a possibility to reduce the costs of CDC synthesis by employing low quality SiC byproducts stemming from the ESK process is presented. While the crystallinity and impurity content differs for the different precursor qualities, the resulting CDC materials possess similar textural characteristics and carbon microstructures. Evaluation of intrinsic kinetic data reveals that the low grade precursors react faster during reactive extraction and can be best described by a power law approach. The CDC materials were further investigated with respect to their performance as electrode materials in Electric Double Layer Capacitors (EDLC). All SiC-CDCs display a comparable and excellent specific capacitance of approx. 115Fg-1. The results are demonstrating the promising utilization of CDC materials synthesized from low valuable SiC feedstock.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; ESK process; Kinetic study; Reactive extraction

Separation of alkane isomers in a hierarchically structured 3D-printed porous carbon monolith - Henrique, Adriano; Steldinger, Hendryk; de Tuesta, Jose L.Diaz; Gläsel, Jan; Rodrigues, Alírio E.; Gomes, Helder T.; Etzold, Bastian J.M.; Silva, José A.C. (Chemical Engineering Journal, 2023)
Hierarchically structured 3D printed porous carbons monoliths, exhibiting cylinder structures composed of tetragonal cubic centered unit cells, were studied for their applicability in adsorptive pentane (C5) and hexane (C6) alkane isomers separation (linear/branched). Three materials of the same macroscopic shape were employed in the study, which varied in the micro- and mesoporosity by changing the final CO2 activation step: non-activated and activated at 1133 K for 6 and 12 h, respectively. Fixed bed breakthrough experiments were conducted for C5/C6 isomer feed mixtures, covering 373, 423, and 473 K temperatures and total alkane partial pressure up to 50.0 kPa. Results demonstrated that the initial porosity for the non-activated monolith enables the complete separation of linear from their respective branched isomers (slightly adsorbed) via a near molecular sieving effect, showing the following sorption hierarchy order (nC6 > nC5) ≫>≫ (2MP > 3MP > 23DMB ≈ iC5 > 22DMB). Regarding the CO2-activated monoliths, both showed a completely different picture, being all the alkane isomers adsorbed (much higher loadings) following the sorption hierarchy order: nC6 > 3MP > 2MP > 23DMB > 22DMB > nC5 > iC5. These results indicate that besides enhancing the microporosity and available specific surface area, the pore sieving effect of branched alkanes is lost due to the pore widening during the CO2 activation. The breakthrough data for the non-activated monolith is also numerically fitted with a convenient, dynamic adsorption model.
CRIS-Team Scopus Importer:2023-08-15
Keywords: 3D-printed carbon monoliths; C5/C6 alkane isomer separation; Fixed bed adsorption; Molecular sieving; Numerical modeling

Simulative Approach for Linking Electrode and Electrolyte Properties to Supercapacitor Performance - Krois, Konrad; Hüfner, Lucas; Gläsel, Jan; Etzold, Bastian J.M. (Chemie Ingenieur Technik, 2019)
Supercapacitors as energy storage devices show distinct advantages like high power density and high cycle stability. While in current applications, mainly the high power density is leveraged, future non-mobile storage devices could also benefit from the robustness and materials employed, while lower charging/discharging time constants are acceptable. In this study, a simulative approach is employed to investigate the complex interplay of mass transfer, electric losses, double layer capacitance for different electrode thicknesses, electrode and electrolyte conductivities as well as charging/discharging time constants. Within the simulation cyclic voltammetry, galvanostatic cycling as also electrochemical impedance spectroscopy experiment could be realized, showing the dependency of achievable maximum capacitance and voltage efficiency on various properties.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Conductivity; Electrode layer thickness; Electrode optimization; Simulation; Supercapacitor